Model Penerapan Kerangka Kualifikasi Nasional Indonesia (KKNI) Sebagai Penguatan Mutu Program Studi Pendidikan Bahasa Arab - ., Nurhadi; Setiyawan, Agung (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
This study aims to compare the two KKNI-based Arabic Language Education curricula between PBA UIN Malang and PBA UMY. This type of research is field research which is located in PBA UIN Maulana Malik Ibrahim Malang and PBA Universitas Muhammadiyah Yogyakarta. Data collection methods using observation, interviews and documentation and data analysis are qualitative. The results of the study show that there are several similarities and differences between the two curricula which are reflected in the curriculum preparation, implementation and evaluation and also found the advantages that are characteristic of each. In addition, there are still some shortcomings because it is indeed a new curriculum that needs to be refined. We hope that this work can be used as a reference as well as learning material for other Arabic Language Education study programs in developing an IQF-based curriculum.